Erythroderma: analysis of 247 cases - Cidia Vasconcellos; Paula P. Domingues; Valéria Aoki; Ricardo K. Miyake; Naim Sauaia; José Eduardo C. Martins
The profile of 247 patients with erythroderma during a 23 year period from January, 1962 through March, 1985, with a follow-up period ranging from 1 to 26 years were analysed. The patients presented with diffuse erythema, scaling and pruritus of more than 2 months' duration, and the age ranged from 16 to 60 years. Psoriasis was the most frequent underlying disease with an estimated frequency of 44.9%, the reaction to the use of drugs appeared in 7.3% of total cases and association with reticulosis showed a frequency of 4.1%. The cause of the erythroderma could not be determined in 29.2% of the cases. Sex differences in terms of underlying diseases were not observed. One or more skin biopsies along with the clinical findings were diagnostic or suggestive of the underlying disease in 63.6% of the cases. Repeated skin biopsies are recommended as the best method for etiologic diagnosis of erythroderma. At P=0.05 significance level, masculine/feminine ratio of 2 : 1 was found. The question arises wether causal agent of erythroderma may not be somehow related to different exposure by sex to environmental antigens.